Substrate treatment for the increment of electric power potential from plants microbial fuel cells. (2021)
Plants microbial fuel cells (PMFC) is novel sytem that generates renewable, clean, and sustainable electricity with minimal environmental impact. However, PMFC has limitations in power generation and current density, since its production values is lower than other renewable technologies. Different studies show that the highest limitation for energy generation through MFC is the high resistivity of the cathode, and the solution is to replace the metallic electrodes with non-metallic materials to obtain a better performance, however, the application of these materials requires complex interdisciplinary work. This study conducted three experimental tests using metallic electrodes for the extraction of electrons and combined a black earth substrate with different natural materials, types of plants, and water to determine their influence in the increment of the electric power output.